Identity politics in Jammu and Kashmir - Chowdhary, Rekha (Vitasta Publ., 2010)
section 1. Identities and politics in Jammu and Kashmir -- section 2. Religion, identities and inter-community relations -- section 3. Exodus and identity politics of Kashmiri pandits -- section 4. Identity politics of women and dalits -- section 5. The other Kashmir